A Review of Sustainable Maintenance in the Manufacturing Companies - Norsiah Hami; Shafini Mohd Shafie; Salmah Omar; Yousif Munadhil Ibrahim; Susan Sabah Abdulameer; Mohd Razali Muhamad (International Journal of Supply Chain Management, 2020)
Owing to the incorporation of sustainability in most organizational activities and processes, their integration into maintenance activities has become a necessity in manufacturing companies. By supporting the implementation of sustainable manufacturing practices, sustainable maintenance will help in improving the sustainability performance of manufacturing companies. The purpose of this study is to review the previous studies related to sustainable maintenance (SMa) in the manufacturing sector in developed and developing countries. Performing content analysis with various past studies conducted in developed and developing countries with several research settings, this study classified SMa into four dimensions that are technical dimension, economic dimension, environmental dimension, and social and safety dimension.  Most of the studies in SMa were conducted using qualitative research design especially case studies while the quantitative studies were still lacking. Besides, the studies more focus on large manufacturing companies compared to Small and Medium Enterprises (SMEs), especially in Malaysia. Therefore, this study presented a research direction on studying the effect of SMa on the sustainability performance of manufacturing SMEs in Malaysia.